Sonification of geometry - Lee, Jian En (Nanyang Technological University, 2023)
Hearing is one of the five main senses of the human body. As such it makes sense to explore ways in which we can use sound to our advantage. However, there are certain aspects of our current methods that make them less suitable. One aspect is the unpleasant nature of simply playing a simple frequency. Thus, it is important to find ways to generate more pleasant-sounding sounds during the exploration of such data. This paper aims to explore ways of recreating music notes, specifically that of a guitar in real life using advanced technology.